Correction: Methodological approach to the ex vivo expansion and detection of T. cruzi-specific T cells from chronic Chagas disease patients. - Gonzalo R Acevedo; Silvia A Longhi; Alcinette Bunying; Nazila Sabri; Augusto Atienza; María P Zago; Radleigh Santos; Valeria A Judkowski; Clemencia Pinilla; Karina A Gómez (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0178380.].